The organic food market as a factor in the development of tourism in the Republic of Serbia: DOI: 10.5937/etp2404001V - Vehapi, Semir; Šabotić, Zenaida (Ekonomija - teorija i praksa, 2025)
An increasing number of modern tourists are demonstrating concern for their health and the environment through their choice and consumption of organically produced food. This suggests that organic production, grounded in the principles of sustainable development, holds significant potential for tourism growth, particularly in agro-eco tourism. Therefore, the main aim of this study is to identify the relationship between organic production and tourism and to highlight its benefits for the tourism sector in Serbia. The relationship was analyzed using correlation analysis. The research is based on data from the FiBL database, as well as from the Ministry of Agriculture, Forestry and Water Management and the Republic Institute of Statistics of Serbia. The findings indicate that expanding organic production areas positively influences tourist arrivals, while an increase in certified organic producers has a positive impact on both arrivals and overnight stays. In conclusion, the study outlines the limitations of the research and provides recommendations for more effective utilization of Serbia’s tourism potential.